Postmodern tricksters: a comparative approach to contemporary picaresque literature - Grazi, Alessandro (Incontri. Rivista europea di studi italiani, 2018)
Review of: Luigi Gussago, Picaresque Fiction Today – The Trickster in Contemporary Anglophone and Italian Literature, Leiden/Boston, Brill/Rodopi, 2016, 305 p., ISBN: 9789004311220, € 126,00.